Analisis Konsep Sejarah (Bernard Lewis) dan Filsafat Strukturalisme: Kajian Makna Simbolis Temuan Candi di Situs Batujaya - Sidqi Alfarez; Nur’aeni Marta (Universitas Hamzanwadi, 2024)
The Batujaya site is one of the relics that reveal the historical heritage of Indonesia in the Hindu-Buddhist era. The objectives of this study are to; 1) Analyzing the study of historical concepts (Bernard Lewis in the case at the Batujaya Site and 2) Reviewing evidence of historical findings) at the Batujaya Site through the philosophy of structuralism (meaning of symbols in the temple area. This research uses qualitative methods (case study approach) through observation, interviews, and excavation reports. The results of the study stated that in the historical concept of Bernard Lewis related to the history of rediscovered has a connection with the discovery at the Batujaya Site which reveals lost history, and can be found by being reconstructed by historians through archaeological reports that have contributed to the collective memory of the Indonesian nation. In addition, the discovery at the Batujaya Site has structuralism meaning as evidenced by the existence of a temple stupa or Vivote Table symbolically about the beliefs of Buddhism.